Identifikasi Potensi Kopi Jahe Sebagai Oleh-Oleh Khas Betawi - Heni Pridia Rukmini Sari (Destinesia : Jurnal Hospitaliti dan Pariwisata, 2019)
Jakarta is a melting pot of cultures from various ethnics and also foreign countries. Even so, Jakarta also has a native population, namely the Betawi ethnic group, who now mostly live on the outskirts of Jakarta because of the development of the capital region. Betawi cuisine is part of an integral Betawi tribe. This Betawi culinary can become one of Indonesia's superior cultural potentials that has special characteristics, high quality and identity, and has a creative ethos and differs creativity, as well as added value economically, technologically and culturally.This research identifies the potential of Betawi culinary to support Jakarta tourism. In addition to culinary, souvenirs can be brought in the form of food and crafts that reflect cultural character. The research method was carried out using a qualitative approach with a grounded theory method. Researchers conducted a desk study activity on culinary tourism potential, compiled a list of Betawi culinary potentials, confirmed the potential of the interviewees (snacks, main food, lunch, dessert, drinks) and made conclusions. The report preparation method is carried out using literature study, field observations, and discussions with informants in the field from the Betawi Women's Association, Betawi Cultural Institute (LKB), Betawi culinary entrepreneurs, and the Jakarta Tourism Office.The achievement of this research is the identification of Ginger Coffee to be used as a potential for souvenirs typical of Betawi which contain locality elements as a basis for developing tourism destinations in Jakarta in particular and Indonesia in general.